Implementasi Algoritma AES dalam Mengenkripsi Berkas Terintegrasi dengan Layanan Cloud Storage Berbasis Android - Dedi Kurniawan; Rita Afyenni; Rahmat Hidayat (Ikatan Ahli Informatika Indonesia, 2018)
In the development of increasingly advanced technology, the security of a data is something that must be considered in maintaining the confidentiality of information. The data contained in the file contain information that can only be known by certain parties. In general, files are stored or shared into a storage that can be accessed using the internet or known as cloud storage. There are ways to secure information on a file so that it cannot be hacked or read to unauthorized parties, namely by using cryptographic methods. Cryptography is a technique to improve the security aspect of information. Cryptography is used to convert information that can be read into unreadable and return an information that was previously unreadable to be legible. In this study cryptography uses the Advanced Encryption Standard (AES) algorithm and Google Drive cloud storage services.